PHENOMENOLOGY OF KINANSYAH GROUP'S PRODUCT MARKETING EXPANSION THROUGH ANALYSIS OF 7P MARKETING MIX - Abdus Salam; Budi Santoso; Feti Fatimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The housing industry in Jember Regency is experiencing a rapid urbanization phenomenon with a backlog of millions of units, where PT Kinansyah Group has managed to dominate the market through adaptive marketing expansion that combines the 7P Marketing Mix strategy with the local cultural values of Pendalungan. This phenomenon of Local Resonance can be seen from the transformation of housing from a physical commodity to a symbol of social status and emotional security, supported by high-tech digitalization but still maintaining a high-touch personal touch typical of Java-Madura friendship. This study analyzes the phenomenology of PT Kinansyah Group's product marketing expansion in Jember Regency through the 7P Marketing Mix approach contextualized with Service Dominant Logic (SDL). Using a qualitative phenomenological method with in-depth interviews, observations, and data triangulation on management informants and consumers, it was found that the success of the expansion was based on Local Resonance through the privatization of the 7P: Product as a status symbol, Flexible price empathy, Place vision of the future, Promotion of relational getok contagion, People seduluran, Process seamless humanist, and Physical Evidence of early legitimacy. The main phenomena include Territorial Psychology, High-Touch High-Tech, Symbolic Materials, and Resilience Adaptation, forming an ecosystem of trust that transforms housing into emotional-social value, so that this strategy dominates the Jember local market through Local Market Mastery with recommendations for digitization of processes and stakeholder collaboration